JEWELL PARKER RHODES’ BLACK BROTHER, BLACK BROTHER: A DEPICTION OF RACIAL STIGMA - Krismala, Dian; Fitria, Sari (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
This study aims to analyze the racial stigma of the main character in the novel Black Brother, Black Brother (2020) written by Jewell Parker Rhodes. It focuses on the stigmatizing action done by Whites against the biracial black kid. As a guide for this study, the theory uses the perspective of Erving Goffman (1963). This study applies qualitative research that collects data from different sources to analyze and support the object of this study. The results showed in this study are the main character experiences racial stigma actions like cynical stares, underestimation, and taunt by society. He took some steps such as avoiding contact with society, showing the achievement, self-isolation, and feeling guilty to respond to the racial stigma